(untitled) (AYUSHDHARA, 2017)
Any abnormality in Rutuchakra (menstrual rhythm) leads excessive and irregular uterine bleeding which is known as “Asrugdara” in classical text. In routine practice of Striroga and Prasutitantra number of patients present with excessive and irregular bleeding vaginally. To study the effect of Sharpunkhamulachurna with Tandulodak in Asrugdara. Asrugdara gives rise to various systemic and psychological disorders which needs treatment. 30 patients were diagnosed with symptoms of Asrugdara attending OPD of our institute and fulfilling criteria are taken for the study. A special proforma was prepared with all points of history taking, physical signs and symptoms and lab. Investigations. The parameters were scored on the basis of standard methods of statistical analysis. In the study, Artavapraman shows 78.8% of relief, Rajastarvaavadhi shows 49.0% of relief, Daha shows 36.9% of relief, Adhoudarshula shows 59.2% of relief, interval between 2 cycle shows 0% of relief, consistency of bleeding shows 44.8% of relief, Varna shows 41.1% of relief and by wilcoxon test it is found that it is highly significant. So it can be concluded that efficacy of Sharpunkhamula churna is significant in Asrugdara on this symptom. Among the available treatment for Asrugdara, Sharpunkhamulachurna is beneficial in curing the vitiated Doshas. The treatment which includes Sharpunkhamulachurna which have been used based on their properties like Tikta and Kashayarasatmak which helps in Stambankarma, it is also Vatakaphaghna - all these objectives are fulfilled to the greater extent.